Gender differences in salespeople: Implications for sales organizations - Chakrabarty, Subhra (2020)
A national random sample of insurance salespeople was surveyed to assess their selling skills and theory of mind capabilities including rapport building, taking a bird’s – eye view, detecting nonverbal cues, and shaping the interaction. The purpose of the study was to explore gender differences in insurance salespeople. An email survey was sent to 9,735 members of the National Alliance for Insurance Education and Research. After several waves of follow-up emails, 324 responses were obtained. The results indicated that female salespeople were better in nonverbal communication than their male counterparts and possessed significantly higher levels of interpersonal skills. The female respondents also self-reported their performance was higher than male salespeople. Based upon these findings, sales organizations should strongly consider hiring female salespeople when selling services. Also, female salespeople may be more advantageous in functional sales organizations compared to the traditional geographic sales organizational structure.